Implementation of Electronic Industrial Training Application for Industrial Training Management Based on Netbeans and Android - Devi Handaya; Pranoto Budi Laksono; Muhammad Ridwan Arif Cahyono (Jurnal Pekommas, 2019)
The research builds a management information system software that can be used by organizer and trainees in the industry. Training information system that aims to improve the effectiveness of managing industrial training and improve employee access to competency information and industry training. It is expected that there will be an increase in employee competencies so that it has an impact on increasing industrial production. The e-IndT application is designed in the form of applications for organizer and training participants. The design of e-IndT application was tested using the balckbox method and questionnaire. Testing on the e-IndT training application for training organizer in the form of time to search for data access, enter data, update data, delete data, and send data via e-mail and SMS then compared with classical systems. Testing on the e-IndT application for training participants in the form of a questionnaire with a quantitative approach. The results of the study stated that the effectiveness of the management of industrial training increased with the processing time in e-IndT applications faster than classical systems. Increasing training participants' access to competency and industry training information is achieved as evidenced by more than 95% of respondents stating the ease of accessing training information.